The Influence of Information Framing towards Investors Reaction in Bullish and Bearish Market Condition: an Experiment - Rahayu, Caecilia Wahyu Estining (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2017)
This research aims to test the reaction of the investors when the investors receive a dividend information presented with positive or negative frames at the same market conditions, either bullish or bearish market conditions. In addition, it also test the reactions of investors when they are in the bullish or bearish market conditions, the investors receive a dividend information with the same frame, both positive and negative frames. The investors reaction is indicated by the magnitude of the stock price prediction on the next day with absolute value. Experimental method is used to test the hypotheses in this research by using independent sample t-test. The results showed that there is an information framing effect to the investors when receiving the information with a positive frame in the bullish market conditions and gain domain effects occur to the investors in the bullish market conditions when the investors receive the information with a positive frame. These results are expected to provide a new insight on the different reactions of investors when receiving the same information.